Queen's Park West, Port of Spain, Trinidad - (:unkn) unknown (My University, 2010)
The sidewalk that runs around the perimeter of the Queen's Park a popular haunt for casual strollers. This postcard is addressed to C. Russell of Sterling, Illinois, U.S.A.
Colour: Coloured (Handpainted); Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; [1912]; Savannas--Trinidad and Tobago; Trees--Trinidad and Tobago; Fences--Trinidad and Tobago; Roads--Guard fences; Pedestrians--Trinidad and Tobago; Roads--Trinidad and Tobago; Palms--Trinidad and Tobago; Roofs--Trinidad and Tobago; Buildings--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Queen's Park Savannah (Port of Spain)